Analysis of the physiological response in junior tennis players during short-term recovery: understanding the magnitude of recovery until and after the 25 seconds rule - Morais, J.E. (2022)
Literature lacks evidence about the physiological recovery of tennis players between points. This study aimed to: (i) verify the heart rate (HR) and oxygen uptake (V̇O2) recovery variance in young tennis players from the end of a tennis drill until the 25-s mark and onwards (65-s limit), performed at several intensities, and (ii) test the curve fitting that better characterizes the players’ HR and V̇O2 recovery, from the end of the drill until the 65-s mark. The sample was composed of 13 male tennis players (age: 16.80 ± 1.61 years) recruited from a National Tennis Association. Players were instructed to perform a drill test (“two-line drill wide mode”) based on an intensity increment protocol. Three levels of intensity were used based on the reserve HR and V̇O2. A significance level effect was observed on the HRreserve and V̇O2reserve (P <.001). At all three levels of intensity, the first 25 s were enough to significantly (P <.001) recover the HRreserve and V̇O2reserve. The same significance trend (P <.001) was maintained until the 65 s but with a lower magnitude over time. Overall, the HR and V̇O2 curve fitting indicated a cubic relationship at the three levels of intensity (except the V̇O2 at the first level). Considering the specific test performed, players significantly elicited their physiological profile for every additional 10 s (after the 25-s rule) in the three levels of intensity performed. Despite this being a drill test and not a competitive point, coaches, players, and tennis organizations should be aware of these findings